Antifouling Activity of Simple Synthetic Diterpenoids against Larvae of the Barnacle Balanus albicostatus Pilsbry - Chen, Jun-De (Molecules, 2010)
Five new pimarane diterpenoids 1-5 were synthesized using ent-8(14)-pimarene-15R,16-diol as starting material. The structures were elucidated by means of extensive NMR and MS analysis. The antifouling activity against larval settlement of the barnacle Balanus albicostatus were evaluated using capsaicin as a positive control. Compounds 1-3 and 5 showed more potent antifouling activity than capsaicin. Compound 5, which exhibited almost the same antifouling activity as starting material, showed better stability than starting material. These compounds all showed antifouling activity in a non-toxic way against larval settlement of the barnacle B. albicostatus. Analysis of structure-activity relationships (SAR) demonstrated that the substituents on the C-15 and C-16 position of pimarane diterpenoid were responsible for the antifouling activity.